(untitled) (Global Journal of Human-Social Science, 2025)
This work aims to discuss how two contemporary philosophical traditions can be used to rethink educational practice in contemporary philosophy It will challenge the appropriation of the theory of humanization in modern and Western philosophy to establish a concept of educational practice that is rooted in human values of plurality and difference Therefore it will be divided into three sections The first deals with a critique of the discourses on humanization in Brazilian educational theorists focusing on F Brayner Brayner 2010 and A Veiga-Neto s Veiga-Neto 2015 elaborations on the duality of theory and practice and their ties to Plato s original version of Western metaphysics In the second section it aims to demonstrate that this criticism is a component of the convergence that links Hannah Arendt s concept of plurality as a human condition that involves our integration into the plural human world and the argument of difference posited by post-structuralist authors such as Michel Foucault Gilles Deleuze and Jacques Derrida who explore the concept of fixed meanings and stable structures in language culture and society Finally these two theoretical traditions will be employed to present the outlines of a notion of educational practice in accordance with three postulates a the assertion that education is a domain where specific regularities and rationalizations occur b the consideration of language as a tool that enables the imagining of alternative methods of expressing and conducting education and c the recognition that educational practice is a location where human values of plurality and difference are learned which emphasizes G Biesta s humanization position Biesta 2013 which shifts the focus from the question of what constitutes a human subject to the question of how the human subject assumes a presence